3D printing technology of continuous fibre reinforced polymeric composites for key load carrying structural parts and components - Zhuo, Peng (2020)
In recent years, 3DP technology has developed to include composite materials. Most of the development to date in this area has involved particulate or short fibre reinforced composites, whilst continuous fibre printing remains a relatively novel research area. By employing continuous fibre as a reinforcement for the composite, the mechanical properties of the printed part can be improved greatly. More importantly, fibre steering can be achieved by the new technology, which brings new possibilities and challenges to composite materials and structures.